Prevailing PA Mutation K356R in Avian Influenza H9N2 Virus Increases Mammalian Replication and Pathogenicity - Xu, Guanlong; Zhang, Xuxiao; Gao, Weihua; Wang, Chenxi; Wang, Jinliang; Sun, Honglei; Sun, Yipeng; Guo, Lu; Zhang, Rui; Chang, Kin-Chow; Liu, Jinhua; Pu, Juan (Journal of virology, 2016)
Adaptation of the viral polymerase complex comprising PB1, PB2, and PA is necessary for efficient influenza A virus replication in new host species. We found that PA mutation K356R (PA-K356R) has become predominant since 2014 in avian H9N2 viruses in China as with seasonal human H1N1 viruses. The same mutation is also found in most human isolates of emergent avian H7N9 and H10N8 viruses whose six internal gene segments are derived from the H9N2 virus. We further demonstrated the mammalian adaptive functionality of the PA-K356R mutation. Avian H9N2 virus with the PA-K356R mutation in human A549 cells showed increased nuclear accumulation of PA and increased viral polymerase activity that resulted in elevated levels of viral transcription and virus output. The same mutant virus in mice also enhanced virus replication and caused lethal infection. In addition, combined mutation of PA-K356R and PB2-E627K, a well-known mammalian adaptive marker, in the H9N2 virus showed further cooperative increases in virus production and severity of infection in vitro and in vivo . In summary, PA-K356R behaves as a novel mammalian tropism mutation, which, along with other mutations such as PB2-E627K, might render avian H9N2 viruses adapted for human infection. IMPORTANCE Mutations of the polymerase complex (PB1, PB2, and PA) of influenza A virus are necessary for viral adaptation to new hosts. This study reports a novel and predominant mammalian adaptive mutation, PA-K356R, in avian H9N2 viruses and human isolates of emergent H7N9 and H10N8 viruses. We found that PA-356R in H9N2 viruses causes significant increases in virus replication and severity of infection in human cells and mice and that PA-K356R cooperates with the PB2-E627K mutation, a well-characterized human adaptive marker, to exacerbate mammalian infection in vitro and in vivo . Therefore, the PA-K356R mutation is a significant adaptation in H9N2 viruses and related H7N9 and H10N8 reassortants toward human infectivity.